Numerical Modelling Of Air Bubbles In Artificial Riffle Zone Using Flow-3d - Khor, Hao Zhe (Universiti Sains Malaysia, 2021)
The Artificial Riffle Structures (ARS) is one of the many methods used in river rehabilitation projects. ARS provides various advantages such as creating complex habitats, regulating water temperature and increasing dissolved oxygen (DO) level in water. DO level can be increased in water by increasing the life-time of air bubbles and entrained air volume. This study serves to investigate the effect of surface shape of ARS unit and arrangement of ARS units in increasing DO level in water. The performance of the ARS in increasing the life-time of air bubble and entrained air volume under three different surface shapes of ARS unit i.e. the flat, pyramid and sphere surface and two different arrangements of ARS were investigated in this study. The three-dimensional (3D) model of each arrangement with different surface shape of ARS unit were produced using the AutoCAD-3D. A commercial computational fluid dynamics (CFD) software, i.e. the Flow-3D, was used to simulate the flow over the ARS zone. From the results obtained, the ARS unit with the sphere shaped surface and the second type of ARS arrangement produced the highest life-time of air bubbles of and entrained air volume. The highest life-time of air bubbles obtained was 9.459s and highest entrained air volume obtained was 0.108024 m3.